2016
DOI: 10.1007/s11306-016-1129-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating sterols as predictors of early allograft dysfunction and clinical outcome in patients undergoing liver transplantation

Abstract: IntroductionSensitive and specific assessment of the hepatic graft metabolism after liver transplantation (LTX) is essential for early detection of postoperative dysfunction implying the need for consecutive therapeutic interventions.ObjectivesHere, we assessed circulating liver metabolites of the cholesterol pathway, amino acids and acylcarnitines and evaluated their predictive value on early allograft dysfunction (EAD) and clinical outcome in the context of LTX.MethodsThe metabolites were quantified in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Herein, we found a decreased level of some fecal sterols, including campestanol, β-sitosterol, and stigmasterol. Although campestanol was not described within kidney dysfunction, low ratios of circulating β-sitosterol and stigmasterol were found by Ceglarek and co-workers [28] in line with our results. We suggest that this alteration might be associated with a high risk of allograft dysfunction and impaired clinical outcome following kidney transplantation.…”
Section: Relevant Metabolites Highlightedsupporting
confidence: 93%
“…Herein, we found a decreased level of some fecal sterols, including campestanol, β-sitosterol, and stigmasterol. Although campestanol was not described within kidney dysfunction, low ratios of circulating β-sitosterol and stigmasterol were found by Ceglarek and co-workers [28] in line with our results. We suggest that this alteration might be associated with a high risk of allograft dysfunction and impaired clinical outcome following kidney transplantation.…”
Section: Relevant Metabolites Highlightedsupporting
confidence: 93%
“…In connection with early allograft dysfunction and primary non-function, DCD grafts appeared to show higher concentrations of lysophosphatidylcholines (lysoPCs) and increased levels of circulatory tryptophan and kynurenine at the pre-transplant stage but lower concentrations of lysoPCs at the post-transplant stage [13,14]. Ceglarek et al [15] have also demonstrated that low esterification of plant sterols in recipients after deceased donor liver transplantation was associated with a high risk of EAD. We therefore hypothesized that the recovery of liver function after liver transplantation may be linked to a disturbance in the lipid homeostasis, and in this study, we examine the lipidomic profiles in association with the development of EAD in recipients of LDLT.…”
Section: Introductionmentioning
confidence: 99%